Prepandemic levels of cytokines and immunoglobulins and risk of SARS-CoV-2 infection and COVID-19 in the general population of Barcelona - Miquel Porta; Miquel Porta; Miquel Porta; Miquel Porta; Miquel Porta; Miquel Porta; José Pumarega; José Pumarega; José Pumarega; Ruth Aguilar; Ruth Aguilar; David Prieto-Merino; et al. (Frontiers in Public Health)
BackgroundFrom a public health perspective it is remarkable that there are yet no longitudinal studies in the general population investigating the influence of the basal immune state, measured before the pandemic, on the risk of SARS-CoV-2 infection and COVID-19.ObjectiveTo investigate the specific and combined effects of personal levels of cytokines and immunoglobulins—measured in individuals’ blood 4 years before the pandemic—on the risk of SARS-CoV-2 infection and COVID-19 in a general population.MethodsWe conducted a prospective cohort study in 240 individuals from the general population of Barcelona. Thirty cytokines and 31 immunoglobulins were quantified in prepandemic serum samples (collected in 2016–17) by high-throughput multiplex quantitative suspension array technology.ResultsHigher concentrations in 2016–17 of IL-8 and TNF-α significantly decreased the risk of SARS-CoV-2 seropositivity in 2020–21, whereas higher concentrations of MIP-1α were a risk factor for seropositivity. Most cytokines in mixtures with IL-8, MIP-1α, TNF-α or G-CSF were associated with SARS-CoV-2 seropositivity (all OR ≥2.0 or OR≤0.4 and p < 0.05). The five individual isotype-antigen pairs more clearly associated with seropositivity were: protectively, IgG to CMV pp150, IgG to CMV pp65, and IgG to N OC43; and, increasing risk of seropositivity, IgM to CMV pp65 and IgM to EBV EA-D. The four cytokines most consistently associated with the risk of COVID-19 were also G-CSF, IL-8, TNF-α, and MIP-1α. The four isotype-antigen pairs more strongly associated with risk of COVID-19 (all protective) were IgA to CMV pp65 and N 229E, and IgG to EBV EAD and VCAp18.ConclusionThe unique longitudinal design of this study, with measurements before and during the pandemic in a general population, provides novel knowledge on the protective and detrimental effects of specific individual cytokines and immunoglobulins, and their mixtures, on the risk of SARS-CoV-2 seropositivity and COVID-19. If confirmed, findings would be significantly relevant for medicine and public health.